The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 Please make a donation to keep the OEIS running. We are now in our 56th year. In the past year we added 10000 new sequences and reached almost 9000 citations (which often say "discovered thanks to the OEIS"). Other ways to donate

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A176854 Sequence defined by the recurrence formula a(n+1)=sum(a(p)*a(n-p)+k,p=0..n)+l for n>=1, with here a(0)=1, a(1)=0, k=-1 and l=0. 1
 1, 0, -2, -7, -18, -37, -52, 10, 412, 1865, 5740, 12922, 16092, -29767, -290264, -1213217, -3608342, -7564363, -6023704, 38816098, 259037300, 991747431, 2756105680, 5061761997, 284694486, -47403203725, -254747436848 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,3 LINKS FORMULA G.f f: f(z)=(1-sqrt(1-4*z*(a(0)-z*a(0)^2+z*a(1)+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z) (k=-1, l=0). Conjecture: (n+1)*a(n) +(-7*n+2)*a(n-1) +(19*n-29)*a(n-2) +(-17*n+40)*a(n-3) +2*(2*n-7)*a(n-4)=0. - R. J. Mathar, Mar 01 2016 EXAMPLE a(2)=2*1*0-2=-2. a(3)=2*1*(-2)-2+0-1=-7. a(4)=2*1*(-7)-2+2*0*(-2)-2=-18. MAPLE l:=0: : k :=-1 : m:=0:d(0):=1:d(1):=m: for n from 1 to 30 do d(n+1):=sum(d(p)*d(n-p)+k, p=0..n)+l:od : taylor((1-sqrt(1-4*z*(d(0)-z*d(0)^2+z*m+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z), z=0, 30); seq(d(n), n=0..30); CROSSREFS Sequence in context: A172188 A077131 A212685 * A086741 A229183 A051743 Adjacent sequences:  A176851 A176852 A176853 * A176855 A176856 A176857 KEYWORD easy,sign AUTHOR Richard Choulet, Apr 27 2010 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified November 29 08:47 EST 2020. Contains 338762 sequences. (Running on oeis4.)